An assessment of John Deere dealership service personnel needs and service managers' perceptions of the John Deere Ag Tech program - Dell, Timothy W. (Kansas State University, 2007)
John Deere Corporation sponsors 16 schools within the United States that are designed to educate students to become future agricultural equipment technicians. At the time of this study, the schools’ enrollments were at a less-than desirable level, 80% capacity. However, the company was receiving feedback that dealerships needed technicians. The need to determine the disparity between the need for technicians and the level of enrollment led to the pursuit of this study. The researcher sampled 306 John Deere agricultural service managers across the continental United States to determine: (a) if the dealerships truly needed technicians, (b) the methods dealerships were using for locating technicians, and (c) the service managers’ perceptions of the John Deere (JD) Ag Tech program. The study also analyzed the relationships between the service managers’ perceptions of the JD Ag Tech program and five independent variables: (a) number of technicians employed at John Deere dealerships, (b) number of stores dealer-organizations own, (c) distance between John Deere dealerships and the closest JD Ag Tech school, (d) number of JD Ag Tech students John Deere dealerships have sponsored, and (e) service managers’ age. The results of the study indicated that John Deere service managers did plan to hire technicians over the next 12 months as well as over the next three years. However, it was also determined that 60% of the service managers were only somewhat knowledgeable or unfamiliar with the JD Ag Tech Program. For the service managers that had experienced sponsoring JD Ag Tech students, those service managers were satisfied with the JD Ag Tech graduates. The researcher’s recommendations focused upon two areas. The first was to improve the marketing of the JD Ag Tech program to insure that all John Deere service managers become familiar with the program. The second recommendation was to focus on improving the “student” component of the partnership, by recruiting the students earlier in their high school careers, and having the partners work together to target high caliber students.
Keywords: John Deere; Partnership; Technician; Recruiting; Needs; Perception; Education, Agricultural (0517); Education, Industrial (0521); Education, Vocational (0747)